Improved solar efficiency by introducing graphene oxide in purple cabbage dye sensitized TiO2 based solar cell - Al-Ghamdi, Ahmed A.; Gupta, R. K.; Kahol, P. K.; Wageh, S.; Al-Turki, Y. A.; El Shirbeeny, W.; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2014)
Natural dye extracted from purple cabbage was used for fabrication of TiO2 dye-sensitized solar cells (DSSCs). The effect of light intensity on the solar efficiency of the device was investigated. It was observed that the efficiency of the DSSC increases with increasing the light intensity e.g. the efficiency of the solar cell increases from 0.013 +/- 0.002% to 0.150 +/- 0.020% by increase in light intensity from 30 to 100 mW/cm(2), respectively. The solar efficiency of the natural dye used in this research was compared with commercial dye (N 719) under similar experimental conditions and observed that the natural (purple cabbage) dye has higher efficiency (0.150 +/- 0.020%) than N 719 (0.078 +/- 0.002%). It was further evaluated that the efficiency of the fabricated solar cell could improve by incorporating graphene oxide. The efficiency of the TiO2 dye-sensitized solar cell was found to increase from 0.150 +/- 0.020% to 0.361 +/- 0.009% by incorporating graphene oxide into purple cabbage dye. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Graphene oxide; Tia(2); AFM; Photovoltaic